KONSEP MUTU DAN MUTU PENDIDIKAN - Haidarul Amjad; Sukirman; Leny Marlina; Febriyant; Adien, Ria (Irfani, 2025)
A multifaceted strategy is essential to enhance education quality. This includes initiatives like bolstering teacher professionalism, creating a curriculum that meets the needs of learners, upgrading facilities and infrastructure, promoting community involvement, and maximizing technology use in educational settings. Through implementing these strategies, the goal is to continually advance the quality of education, producing superior and competitive human resources. Keywords: Quality, Quality of Education, Education Quality Factors